Sistem Informasi Geografis Penyebaran Wabah Covid-19 pada Dinas Kesehatan Kabupaten Bireuen - Mutasar, Irhamullah (LPPM-UNIKI, 2021)
Covid-19 is a type of pandemic that emerged at the end of 2019 which has attacked all over the world, to Indonesia, not to mention the Bireuen-Aceh district. For easier handling it is necessary to socialize 3M and provide social distancinginformation and arrange visits to the danger zone which is divided into five zone levels, namely the green, orange,yellow, red and black zones. Currently, there is a need for geographic-based mapping in Bireuen district to provideinformation on the level of danger of the Covid-19 zone for the general public, especially for the government. Theinformation presented is very complex because it is supported by geographical information through the design of a webapplication that uses the Google Maps API which can provide geographic information through mapping the earth'ssurface that can be accessed through a web application. The geographic information system web application is designedwith the PHP programming language and MySQL database. From the results of the design and implementation of thesystem, it has been able to provide information on the location of the covid-19 zone which is displayed by color so that itcan provide information to the public.